Self-Management, Research and Institutional Support in Timely Graduation: A Systematic Literature Review - Wenti Arum Widasari; I Made Sukresna (LifeSciFi, 2025)
Timely graduation is one of the important indicators in measuring the effectiveness of education. However, its achievement is still a challenge in many institutions. This study aims to explore the influence of self-management, research skills, and institutional support on the timely graduation of master's students using the Systematic Literature Review (SLR) method covering the period 2010 to 2025. The results of the analysis of various literature and scientific articles show that these three variables have a significant influence on research success. Self-management plays a role in managing time and academic responsibility, research skills determine the smoothness of thesis preparation, and institutional support provides an external foundation in the form of policies, facilities, and academic services that support the lecture process. This study concludes that the synergy between internal and external factors of students is key in encouraging an increase in the rate of timely permission. The practical implications of these findings provide recommendations for higher education institutions in designing academic mentoring programs and policy strategies that are more responsive to student needs.